Perancangan Sampul Buku Edukasi Mewarnai Grafiti - Arjuna Dimas Maulana; Aris Sutejo; Aileena Solicitor Costa Rica El Chidtian (Pusat Riset dan Inovasi Nasional, 2026)
Cover Design for an Educational Graffiti Coloring Book. The development of urban visual culture shows a shift in perception of graffiti from mere vandalism to part of contemporary art practices that have visual structure and aesthetic identity. Graffiti's closeness to the expressive character of teenagers makes it a potential visual approach in educational media. This paper aims to design a graffiti-based coloring book cover that can represent the visual character of graffiti in an attractive way and in line with the preferences of teenagers aged 16–18 years. The method used is Design Thinking with a descriptive qualitative approach through the stages of empathize, define, ideate, prototype, and test. Data was obtained through interviews with graffiti practitioners, observation, distribution of questionnaires to 51 respondents, and literature studies related to visual communication design and adolescent development. The design results show that the application of graffiti typography, dynamic composition, illustrations of typical graffiti elements, and the use of contrasting colors can build a strong and communicative visual identity. Validation through an expert review placed the design in the feasible category with several recommendations for improvement.